Noise robust target identification based on the wave-coefficients-2dimension case. (11th November 2016) - Jiang, Xiaomin; Lai, Yingxin; Xia, Mingyao
Abstract: To correctly identify a remote target in a noisy environment is very challenging. Usually, the accuracy of target recognition degrades under the condition of a low signal-to-noise ratio (SNR). Radar target identification based on wave-coefficients (WCs) is proposed and seems to be promising. We introduce the WCs of two-dimensional (2D) targets in this paper. The main problem of WC based target identification is that the extraction of wave-coefficients is an ill-posed problem. Thus the recognition results yielded in the presence of noise is not reliable. The regularization algorithm is exploited to extract the wave-coefficients, the regularization parameter is determined by the L-curve method. Simulation results using 4 2D targets show that the proposed scheme is effective and high target recognition rate is achieved in cases of low SNR scenarios.